Music Therapy - History and Cultural Contexts - Ruud, Even (Voices: A World Forum for Music Therapy, 2001)
An essay review 1 of:Horden, Peregrine (Ed.) (2000). Music as Medicine. The History of Music Therapy since Antiquity. Aldershot: Ashgate.Gouk, Penelope (Ed.) (2000). Musical Healing in Cultural Contexts. Aldershot: Ashgate.